2020
DOI: 10.1128/jcm.01400-19
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Rapid Blood Culture Diagnostic Test in a Children's Hospital Depends on Gram-Positive versus Gram-Negative Organism and Day versus Night Shift

Abstract: Rapid diagnostic tests (RDTs) for bloodstream infections (BSIs) decrease the time to organism identification and resistance detection. RDTs are associated with early deescalation of therapy for Gram-positive BSIs. However, it is less clear how RDTs influence antibiotic management for Gram-negative BSIs and whether RDT results are acted on during off-hours. We performed a single-center, retrospective review of children with BSI and Verigene (VG) testing at a children’s hospital. Of the 301 positive cultures inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…34 Multiple studies have demonstrated reductions in time to de-escalation for treatment of methicillin-susceptible S aureus (MSSA) BSIs upon implementation of molecular assays to detect mecA. [35][36][37] The ability to rapidly differentiate S aureus from CoNS has also been shown to reduce unnecessary antimicrobial administration to patients whose isolates represent contaminants. 35 Taken together, rapid diagnostics with antimicrobial stewardship interventions reduce time to appropriate therapy, but not all studies have been able to demonstrate reduced length of stay or mortality which may be due to limitations in study design or differences in patient populations.…”
Section: Does the Utilization Of Rapid Diagnostics Improve Patient Outcomes?mentioning
confidence: 99%
“…34 Multiple studies have demonstrated reductions in time to de-escalation for treatment of methicillin-susceptible S aureus (MSSA) BSIs upon implementation of molecular assays to detect mecA. [35][36][37] The ability to rapidly differentiate S aureus from CoNS has also been shown to reduce unnecessary antimicrobial administration to patients whose isolates represent contaminants. 35 Taken together, rapid diagnostics with antimicrobial stewardship interventions reduce time to appropriate therapy, but not all studies have been able to demonstrate reduced length of stay or mortality which may be due to limitations in study design or differences in patient populations.…”
Section: Does the Utilization Of Rapid Diagnostics Improve Patient Outcomes?mentioning
confidence: 99%
“…However, whether this rapid turnaround time (TAT) translates into more favorable clinical outcomes remains to be determined. 46 , 47 …”
Section: Rapid Direct Phenotypic Antimicrobial Susceptibility Testimentioning
confidence: 99%
“… 4 , 6 , 8 , 9 Passive reporting of syndromic blood culture panel information results in rapid antibiotic escalation, but deescalation and discontinuation of unnecessary antimicrobials is much slower if it happens at all. 10 , 11 The biggest lesson these outcome studies have taught us is the critical value of antimicrobial stewardship programs in the timely optimization or discontinuation of antibiotics. 12 …”
Section: Detection Of Bloodstream Pathogensmentioning
confidence: 99%